Orthopalladated complexes as phase-transfer catalysts for asymmetric alkylation of achiral Schiff base esters - Kim, Dae Hyun; Im, Jin Kyu; Kim, Dae Won; Lee, Hyunjoo; Kim, Honggan; Kim, Hoon Sik; Cheong, Minserk; Mukherjee, Deb Kumar (SPRINGER, 2010)
The asymmetric C-alkylation of benzophenone Schiff base glycine esters has been achieved using a palladium(II) chiral complex as a phase-transfer catalyst. The aromatic moiety around the metal center and various physicochemical parameters were investigated to study their effect on the asymmetric alkylation reaction under phase-transfer conditions. Moderate enantioselectivity(30-40%) was achieved under room temperature conditions, which is a significant improvement compared to no enantioselectivity with a chiral palladium-salen complex reported earlier. Computer simulation studies indicate that coordination of the metal center with Z-enolate forming a square planar complex provides a favorable steric environment where the alpha-carbon atom of the enolate is available for enantioselective alkylation.
Keywords: ALPHA-AMINO-ACIDS; ENANTIOSELECTIVE SYNTHESIS; AMMONIUM-SALTS; IMMOBILIZATION; DIASTEREOMERS; DERIVATIVES; DIMERS; ROUTE